Management of a granulomatous lesion in a patient with Kindler's Syndrome - Anuradha Bhatsange; Yugandhara Khadse; Sabina Deshmukh; Swapnil Karwa (Wolters Kluwer Medknow Publications, 2018)
Kindler's syndrome is a rare vesiculobullous dermatological disorder sometimes involving multiple organs. First described by Kindler. The differential diagnosis includes Rothmund-Thomson syndrome and epidermolysis bullosa. Fisher's criteria have simplified the diagnosis with major and minor criteria. Oral manifestation of this syndrome includes multiple painful oral ulcers in the mucosa, periodontal attachment loss, gingival bleeding, and fragile mucosa. These manifestations may impair proper nutrition intake, may cause growth and development problems. This case report deals with the management of oral and gingival manifestations in a 12-year-old female child patient diagnosed with Kindler's syndrome.